Pendekatan Menangani Rasuah Menurut Maqasid Syariah - Azman Ab Rahman; Nur Wahida Lokman; Lutfi Mohamed Zain; Setiyawan Gunardi; Syed Mohd Najib Syed Omar (Usuli Faqih Research Centre PLT, 2024)
Vol. 26 No. 2